Implementation of the Colombo wetland management strategy: current status, stakeholder perceptions and recommendations - Chaturangi Wickramaratne; Priyanie Amerasinghe; Matthew Simpson; Radheeka Jirasinha; Matthew McCartney (Wetlands Ecology and Management, 2026)

Likelihood-free parameter inference for spatiotemporal stochastic biological models using neural posterior estimation - Tom Kimpson; Jennifer Flegg; Matthew J. Simpson (Journal of Theoretical Biology, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

How Implementing the Rights of Wetlands Provides Benefits to People and Wetlands: Relationships, Rights, Responsibilities, Experiences, and Actions - Gillian Davies; Ritesh Kumar; M. Siobhan Fennessy; Nick Davidson; Kai Huschke; Dave Pritchard; Matthew Simpson; Priyanie Amerasinghe; William R. Moomaw; Erin Okuno; Bethanie Walder; Chaturangi Wickramaratne; et al. (Wetlands, 2026)
Rights of wetlands shifts the people-wetlands relationship towards one recognizing the intrinsic rights and living beingness of wetlands, embodying reciprocity, kinship, and gratitude. Recognition of wetland rights occurs within the broader Rights of Nature movement, which has often been led by Indigenous Peoples and local communities from many cultural traditions. Intrinsic wetland rights centre on the right to exist and incorporate seven other rights, forming a holistic framework that enables preservation of wetland ecosystem integrity. These rights provide the basis for a wetland’s thriving existence. The eight rights are: • the right to exist. • their natural place in the landscape; • natural and connected hydrologic regimes; • natural climatic conditions; • naturally occurring biodiversity; • natural ecosystem processes; • natural water, soil, and air quality (i.e., structural integrity and form); and. • regeneration and a naturally determined future. Moral and ethical responsibilities towards these rights include fostering harmonious relationships in and with wetlands, respecting interdependence of all wetland components, safeguarding and fostering conditions enabling rights of wetlands, and acting in a precautionary manner when faced with risks of harm to wetlands. Legal and policy responsibilities include acknowledging plural worldviews, recognising legal standing and political orientations to represent and defend wetland rights, providing adequate means for wetland representation and defending and advocating for wetlands, and using best available science to restore degraded wetlands and support regeneration, thereby supporting harmonious societal relationships with wetlands. Opportunities for implementation of rights of wetlands at a variety of scales (individual, community, national, and global) are explored, and training/guidance resources are referenced.

Parameter-wise predictions and sensitivity analysis for random walk models in the life sciences - Yihan Liu; David J. Warne; Matthew J. Simpson (Journal of Theoretical Biology, 2026)

Surface characteristics limit the vertical mobility of an invasive reptile - Thomas W. Simpson; Marleen Baling; Anne C. Gaskett; Richard C. Gibson; Steven Matthews; Jacqueline R. Beggs (Biological Invasions, 2026)
Preventing the spread of small, cryptic invasive reptiles poses an ongoing challenge for conservation and biosecurity worldwide. Physical exclusion barriers offer a potentially low-cost, non-toxic tool for limiting dispersal, but their effectiveness depends on, among other factors, a detailed understanding of how surface properties influence animal movement. We tested four commonly available fencing materials—polypropylene fabric, woven polypropylene, polythene sheet, and acrylic sheet—as potential barriers to climbing by a small Australian skink, Lampropholis delicata (Scincidae). Experiments with 18 adult skinks were conducted in enclosures under both wet and dry conditions. We quantified surface roughness using four metrics: arithmetic average roughness (Ra), total height of profile (Rt), mean spacing of profile irregularities (Rsm) and Skewness (Rsk). Climbing frequency was highest on the roughest material, polypropylene fabric (Ra = 25, Rt = 167, Rsm = 457.5 µm), with up to 60% of individuals climbing. In contrast, the smoother surfaces, polythene and acrylic, limited climbing to just 5% of trials, with climbs occurring only under wet conditions. This suggests that surface water may enhance adhesion and reduce the effectiveness of smooth barriers. Our findings indicate that simple vertical drift fences are unlikely to effectively manage the spread of L. delicata , particularly in wet environments and underscore the importance of incorporating surface roughness thresholds and moisture conditions into barrier design. Polythene sheet, shows promise for indoor containment but would require modifications such as anti-climb lips for outdoor use. Tailored exclusion strategies that integrate material science with animal behaviour and ecological context could offer scalable, environmentally friendly tools for containing and managing invasive species.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

A solution from the past: exploring the untapped potential of museum specimens to preserve secondary metabolites - Sam Afoullouss; Jennifer Netjes; Matthew Simpson; Micah Harris; Laurent Calcul; Dale Chaput; William Keel; Bill J. Baker (Phytochemistry Letters, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Multi-centre normative brain mapping of intracranial EEG lifespan patterns in the human brain - Heather Woodhouse; Gerard Hall; Callum Simpson; Csaba Kozma; Frances Turner; Gabrielle M. Schroeder; Beate Diehl; John S. Duncan; Jiajie Mo; Kai Zhang; Aswin Chari; Martin Tisdall; et al. (Brain Structure and Function, 2025)
Understanding healthy human brain function is crucial to identify and map pathological tissue within it. Whilst previous studies have mapped intracranial EEG (icEEG) from non-epileptogenic brain regions, they often neglect age and sex effects. Further, they are limited by small sample sizes due to the modality’s invasive nature. This study substantially expands the subject pool compared to existing literature, to create a multi-centre, normative map of brain activity which considers the effects of age, sex and recording hospital. Using interictal icEEG recordings from $$n = 502$$ subjects across 15 centres, we constructed a normative map of non-pathological brain activity by regressing age and sex on relative band power in five frequency bands. A linear mixed model was implemented to account for the hospital effect. Variable importance was assessed using standard statistical measures, and regression coefficients (and their standard errors) were analysed at both whole-brain and regional scales. Recording hospital significantly impacted normative icEEG maps in all frequency bands, and age was a more influential predictor of band power than sex. The age effect varied by frequency band, but no spatial patterns were observed at the region-specific level. Certainty about regression coefficients was also frequency band specific and moderately impacted by sample size. The concept of a normative map is well-established in neuroscience research and particularly relevant to the icEEG modality, which does not allow healthy control baselines. Our key results regarding the hospital site and age effect guide future work utilising normative maps in icEEG.

Data-informed model reduction for inference and prediction from non-identifiable models - Matthew J. Simpson (Journal of Theoretical Biology, 2025)

A generalised sigmoid population growth model with energy dependence: Application to quantify the tipping point for Antarctic shallow seabed algae - Elise Mills; Graeme F. Clark; Matthew J. Simpson; Mark Baird; Matthew P. Adams (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Modelling count data with partial differential equation models in biology - Matthew J. Simpson; Ryan J. Murphy; Oliver J. Maclaren (Journal of Theoretical Biology, 2024)

New computational tools and experiments reveal how geometry affects tissue growth in 3D printed scaffolds - Daniel J. VandenHeuvel; Brenna L. Devlin; Pascal R. Buenzli; Maria A. Woodruff; Matthew J. Simpson (Chemical Engineering Journal, 2023)

Integrated Exposure–Response of Dupilumab in Children, Adolescents, and Adults With Atopic Dermatitis Using Categorical and Continuous Efficacy Assessments: A Population Analysis - Emily Briggs; Mohamed A. Kamal; Matthew P. Kosloski; Ian Linsmeier; Natalie Jusko; Nancy Dolphin; Jason Chittenden; Eric L. Simpson; Amy S. Paller; Elaine C. Siegfried; Brad Shumel; Noah A. Levit; et al. (Pharmaceutical Research, 2023)
Background While the majority of patients with atopic dermatitis (AD) achieve disease control with dupilumab treatment, there is variability in which patients achieve clear disease. The predictors of these responses are currently unclear. Integrated models were developed to evaluate the exposure–response (E-R) relationship of dupilumab in children, adolescents, and adults with AD. Methods Data from six Phase II and III clinical studies were pooled (2,366 adults [> 18 years], 243 adolescents [≥ 12 to < 18 years] and 359 children [≥ 6 to < 12 years]) for model development. Efficacy was assessed using the Eczema Area and Severity Index (EASI) and Investigator’s Global Assessment (IGA). Indirect response models were applied to link measures of efficacy and functional serum dupilumab concentrations. The covariates on individual placebo-corrected response were assessed. Clinical trial scenarios were simulated to compare E-R relationships across age groups. Safety was not explored. Results After correcting for differences in placebo response and dupilumab exposure: 1) older age, higher body weight, lower baseline thymus and activation-regulated chemokine, and Asian race were associated with slightly lower EASI response, and no clear covariates were identified on IGA response; 2) clinical trial simulations generally showed slightly higher response at a given dupilumab concentration in children compared to adults and adolescents with severe and moderate AD. Conclusions The collectively tested covariates explain some of the variability in dupilumab response in patients with AD. Patients in all age groups showed adequate response to dupilumab; however, children showed slightly higher drug effects compared to adults and adolescents at equivalent concentrations.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Generalized moisture diffusivity for food drying through multiscale modeling - Zachary G. Welsh; Matthew J. Simpson; Md Imran H. Khan; M.A. Karim (Journal of Food Engineering, 2023)

Genome screening, reporting, and genetic counseling for healthy populations - Selina Casalino; Erika Frangione; Monica Chung; Georgia MacDonald; Sunakshi Chowdhary; Chloe Mighton; Hanna Faghfoury; Yvonne Bombard; Lisa Strug; Trevor J. Pugh; Jared Simpson; Saranya Arnoldo; et al. (Human Genetics, 2023)

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Contrasting Effects of Nitrogen Addition on Leaf Photosynthesis and Respiration in Black Mangrove in North Florida - Matthew A. Sturchio; Jeff Chieppa; Lorae T. Simpson; Ilka C. Feller; Samantha K. Chapman; Michael J. Aspinwall (Estuaries and Coasts, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A critique of “A critical review of critical power” - Matthew I. Black; Len Parker Simpson; Richie P. Goulding; James Spragg (European Journal of Applied Physiology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Small-scale spatial structure affects predator-prey dynamics and coexistence - Anudeep Surendran; Michael J. Plank; Matthew J. Simpson (Theoretical Ecology, 2020)

Small-scale spatial structure influences large-scale invasion rates - Michael J. Plank; Matthew J. Simpson; Rachelle N. Binny (Theoretical Ecology, 2020)

Projected 21st Century Sea-Level Changes, Observed Sea Level Extremes, and Sea Level Allowances for Norway - Matthew Simpson; Oda Ravndal; Hilde Sande; Jan Nilsen; Halfdan Kierulf; Olav Vestøl; Holger Steffen (Journal of Marine Science and Engineering, 2017)
Changes to mean sea level and/or sea level extremes (e.g., storm surges) will lead to changes in coastal impacts. These changes represent a changing exposure or risk to our society. Here, we present 21st century sea-level projections for Norway largely based on the Fifth Assessment Report from the Intergovernmental Panel for Climate Change (IPCC AR5). An important component of past and present sea-level change in Norway is glacial isostatic adjustment. We therefore pay special attention to vertical land motion, which is constrained using new geodetic observations with improved spatial coverage and accuracies, and modelling work. Projected ensemble mean 21st century relative sea-level changes for Norway are, depending on location, from −0.10 to 0.30 m for emission scenario RCP2.6; 0.00 to 0.35 m for RCP 4.5; and 0.15 to 0.55 m for RCP8.5. For all RCPs, the projected ensemble mean indicates that the vast majority of the Norwegian coast will experience a rise in sea level. Norway’s official return heights for extreme sea levels are estimated using the average conditional exceedance rate (ACER) method. We adapt an approach for calculating sea level allowances for use with the ACER method. All the allowances calculated give values above the projected ensemble mean Relative Sea Level (RSL) rise, i.e., to preserve the likelihood of flooding from extreme sea levels, a height increase above the most likely RSL rise should be used in planning. We also show that the likelihood of exceeding present-day return heights will dramatically increase with sea-level rise.

Observed Sea-Level Changes along the Norwegian Coast - Kristian Breili; Matthew Simpson; Jan Nilsen (Journal of Marine Science and Engineering, 2017)
Norway’s national sea level observing system consists of an extensive array of tide gauges, permanent GNSS stations, and lines of repeated levelling. Here, we make use of this observation system to calculate relative sea-level rates and rates corrected for glacial isostatic adjustment (GIA) along the Norwegian coast for three different periods, i.e., 1960 to 2010, 1984 to 2014, and 1993 to 2016. For all periods, the relative sea-level rates show considerable spatial variations that are largely due to differences in vertical land motion due to GIA. The variation is reduced by applying corrections for vertical land motion and associated gravitational effects on sea level. For 1960 to 2010 and 1984 to 2014, the coastal average GIA-corrected rates for Norway are 2.0 ± 0.6 mm/year and 2.2 ± 0.6 mm/year, respectively. This is close to the rate of global sea-level rise for the same periods. For the most recent period, 1993 to 2016, the GIA-corrected coastal average is 3.5 ± 0.6 mm/year and 3.2 ± 0.6 mm/year with and without inverse barometer (IB) corrections, respectively, which is significantly higher than for the two earlier periods. For 1993 to 2016, the coastal average IB-corrected rates show broad agreement with two independent sets of altimetry. This suggests that there is no systematic error in the vertical land motion corrections applied to the tide-gauge data. At the same time, altimetry does not capture the spatial variation identified in the tide-gauge records. This could be an effect of using altimetry observations off the coast instead of directly at each tide gauge. Finally, we note that, owing to natural variability in the climate system, our estimates are highly sensitive to the selected study period. For example, using a 30-year moving window, we find that the estimated rates may change by up to 1 mm/year when shifting the start epoch by only one year.

Wetland Ecosystem Services and the Ramsar Convention: an Assessment of Needs - Robert J. McInnes; Matthew Simpson; Beatriz Lopez; Robbie Hawkins; Robert Shore (Wetlands, 2017)

The effects of pharmacological modulation of the serotonin 2C receptor on goal-directed behavior in mice - Matthew R. Bailey; Cait Williamson; Chris Mezias; Vanessa Winiger; Rae Silver; Peter D. Balsam; Eleanor H. Simpson (Psychopharmacology, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Predicted responses of arctic and alpine ecosystems to altered seasonality under climate change - Jessica G Ernakovich; Kelly A. Hopping; Aaron B. Berdanier; Rodney T. Simpson; Emily J. Kachergis; Heidi Steltzer; Matthew D. Wallenstein (Global Change Biology, 2014)
Global climate change is already having significant impacts on arctic and alpine ecosystems, and ongoing increases in temperature and altered precipitation patterns will affect the strong seasonal patterns that characterize these temperature‐limited systems. The length of the potential growing season in these tundra environments is increasing due to warmer temperatures and earlier spring snow melt. Here, we compare current and projected climate and ecological data from 20 Northern Hemisphere sites to identify how seasonal changes in the physical environment due to climate change will alter the seasonality of arctic and alpine ecosystems. We find that although arctic and alpine ecosystems appear similar under historical climate conditions, climate change will lead to divergent responses, particularly in the spring and fall shoulder seasons. As seasonality changes in the Arctic, plants will advance the timing of spring phenological events, which could increase plant nutrient uptake, production, and ecosystem carbon (C) gain. In alpine regions, photoperiod will constrain spring plant phenology, limiting the extent to which the growing season can lengthen, especially if decreased water availability from earlier snow melt and warmer summer temperatures lead to earlier senescence. The result could be a shorter growing season with decreased production and increased nutrient loss. These contrasting alpine and arctic ecosystem responses will have cascading effects on ecosystems, affecting community structure, biotic interactions, and biogeochemistry.

Estimates of twenty-first century sea-level changes for Norway - Matthew J. R. Simpson; Kristian Breili; Halfdan P. Kierulf (Climate Dynamics, 2014)

A continuous velocity field for Norway - Halfdan Pascal Kierulf; Mohammed Ouassou; Matthew James Ross Simpson; Olav Vestøl (Journal of Geodesy, 2013)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Cannibalism in the lifeboat — collective movement in Australian plague locusts - Matthew J. Hansen; Camille Buhl; Sepideh Bazazi; Stephen J. Simpson; Gregory A. Sword (Behavioral Ecology and Sociobiology, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Ice stream influence on West Greenland Ice Sheet dynamics during the Last Glacial Maximum - David H. Roberts; Antony J. Long; Bethan J. Davies; Matthew J. R. Simpson; Christoph Schnabel (Journal of Quaternary Science, 2010)
This paper investigates the processes governing bedrock bedform evolution in ice sheet and ice stream areas in central West Greenland, and explores the evidence for a cross‐shelf ice stream at the Last Glacial Maximum (LGM). To the east of Sisimiut the formation of streamlined bedforms with high elongation ratios and high bedform density has been controlled by geological structure and topography in slow‐flowing ice sheet areas. At the coast, the effects of regional flow convergence, caused by coastal fjord orientation, routed ice into the Sisimiut/Itilleq area where it formed an ice stream onset zone. This funnelled ice into an offshore trough (Holsteinsborg Dyb), resulting in a southwesterly regional ice flow direction and the formation of a topographically routed ice stream (Holsteinsborg Isbrae). To the south of this, striae and bedform evidence show that local valley glaciers initially flowed east to west across the coast, but were later redirected by the Itilleq Fjord ice which turned southwestward due to diffluent flow and deflection by Holsteinsborg Isbrae. Roches moutonnées in this area have low elongation ratios and high bedform density, but do not provide unequivocal support for ice streaming, as they are a product of both bedrock structure and changes in ice flow direction, rather than enhanced flow velocities. Cosmogenic surface exposure ages limit maximum ice sheet surface elevation to ca. 755–810 m above sea level in this region. Such ice thickness enabled Holsteinsborg Isbrae to reach the mid/outer continental shelf during the LGM, and to contribute to the formation of a trough mouth fan and the Outer Hellefisk moraines. Initial deglaciation across this region was driven by rising sea level and increasing air temperatures prior to the Bølling Interstadial at ca. 14.5 cal. ka BP. Between 12 and 10 cal. ka BP both increased air and ocean temperatures post the Younger Dryas, and peak sea‐level rise up to the marine limit, caused accelerated thinning and marginal retreat through calving, although dating evidence suggests ice streams remained along the inner shelf/coast boundary until at least ca. 10 cal. ka BP, their longevity maintained by increased ice thickness and ice discharge. Copyright © 2009 John Wiley & Sons, Ltd.

Urban effects of Chennai on sea breeze induced convection and precipitation - Matthew Simpson; Sethu Raman; R. Suresh; U. C. Mohanty (Journal of Earth System Science, 2008)

Birds as indicators of wetland status and change in the North Rupununi, Guyana - Jayalaxshmi Mistry; Andrea Berardi; Matthew Simpson (Biodiversity and Conservation, 2008)

Sea-breeze-initiated rainfall over the east coast of India during the Indian southwest monsoon - Matthew Simpson; Hari Warrior; Sethu Raman; P. A. Aswathanarayana; U. C. Mohanty; R. Suresh (Natural Hazards, 2007)

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Reply to comment on “Computing residence times for flow towards a pumping well: nomograph solution and validity of the small draw-down approximation”, Technical Note published in Hydrogeology Journal (2005) 13:889–894 - Matthew J. Simpson (Hydrogeology Journal, 2007)

Computing residence times for flow towards a pumping well: nomograph solution and validity of the small draw-down approximation - Matthew J. Simpson (Hydrogeology Journal, 2005)

Development and propagation of a pollution gradient in the marine boundary layer during INDOEX (1999) - Matthew Simpson; Sethu Raman (Journal of Earth System Science, 2005)

Nitric oxide: potential role for reducing gastro-enteropathy - Matthew Walley; Christoph Hotz-Behofsits; Robert Simpson; Ingvar Bjarnason (Inflammopharmacology, 2003)

Organophosphate neuropathy due to methamidophos: biochemical and neurophysiological markers - Rob McConnell; Edgar Delgado-Téllez; Ricardo Cuadra; Edmundo Tórres; Matthew Keifer; Juan Almendárez; Jamilet Miranda; Hassan A. N. El-Fawal; Mary Wolff; David Simpson; Ingvar Lundberg (Archives of Toxicology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)